Putrajaya and the French connection - Mohd. Ali, Noor Azizi (2007)
Putrajaya, being one of the most significance and distinguished city of its kind in Malaysia is claimed to be of a ‘true and progressive’ Malaysian architectural expression. The architecture of Putrajaya has been drawn upon diverse influences resulting in a building that is uniquely ‘Malaysian-Islamic’ in character and universal in outlook. Above all it represents a fusion of the best of the past and present to create an enduring legacy for the future. Another administration centre of the sort, Versailles of France is an example of an architectural grandeur designed for an absolute monarch Louis XIV. It is resplendent as the prime example of the French baroque style. As with Putrajaya, Versailles is spreads with gardens and forests, added with immaculate parterres, great basins and orangery. This paper is therefore seeking an explanation on the influences and similarity (or imitation?) of both administration centre of Putrajaya and the Versailles. The intention is to gauge the development of Putrajaya architectural language in comparison to the French’s Baroque particularly the city of Versailles. It is hope that the true characteristic is revealed